Group-oriented ciphertext-policy attribute-based encryption with expressive access policy - Yang LI; Jiang-hua LIU; Wei WU (网络与信息安全学报)
Based on the study of the traditional attribute-based encryption,a scheme called group-oriented ciphertext-policy attribute-based encryption was proposed.In the scheme,the access policy consists of AND-gate and OR-gate.Users were split up into different groups.Users from the same group can merge their attributes to decrypt successfully,if the union of their attributes satisfies the access structure embedded in the ciphertext.But users from different groups cannot realize this cooperative decryption.A concrete construction and security model was given.Finally,the security proof for the proposed scheme was given.